ANALISIS CERITA RAKYAT RADEN AYU DEWI NAWANGSIH DAN RADEN BAGUS RINANGKU SEBAGAI PUSAT ZIARAH SERTA TRADISI MASYARAKAT - Ayu Dewi Nafisatul Khofifah; Intan Cahyaningtyas, Ony Khansa’ Khoirunnisa, Mohammad Kanzunnudin (ADISAM PUBLISHER, 2025)
This research discusses folklore about the graves of Raden Ayu Dewi Nawangsih and Raden Bagus Rinangku in Kudus, which are considered spiritual places and have local values for the community. The approach used in this research is qualitative, with a focus on literature review. The purpose of this research is to uncover the history, legends and traditions associated with the tombs. The methods used include document analysis and interviews with pilgrims.The results show that the tomb not only has historical value, but is also a place of pilgrimage that combines beliefs, rituals and moral values. Many pilgrims come to seek blessings, but often the purpose of this pilgrimage is misinterpreted with deviant practices. The tragic story of the two characters should serve as a lesson on the consequences of violating norms. This research emphasizes the importance of properly understanding the spiritual meaning of pilgrimage to maintain noble cultural values, as well as the potential for preserving the tradition as a tourist attraction that still respects local spiritual and cultural values.